2009
DOI: 10.1111/j.1365-2230.2008.03024.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphomatoid papulosis and associated lymphomas: a retrospective case series of 84 patients

Abstract: Referral bias may explain the higher (40%) incidence of lymphoma in this population of LyP patients, compared with the 10-20% incidence commonly cited in the literature. In the subset of patients presenting with LyP alone, only 18% later developed lymphoma. Male patients or patients with prior EBV infection may have a higher risk for developing lymphoma, and some patients improved with treatment of putative infectious triggers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
4
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 23 publications
1
92
4
3
Order By: Relevance
“…The need for prolonged follow-up of patients with LyP is also supported by the high 41% frequency of associated lymphomas in the present study. This rate is higher than the commonly reported 10%-20% rates [3,8,9,[11][12][13][14][15]20], and is in accordance with the results from recent studies by Kunishige et al and Liu et al, who reported much higher rates of associated lymphomas (40% and 61%, respectively) [16][17][18]. It is likely that the high proportion of associated lymphomas in these 2 series and the present study (41%) are due to the prolonged follow-up of patients (17.5, 12.3, and 11.3 years respectively), as compared with series that reported lower rates of associated lymphomas [16,18].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The need for prolonged follow-up of patients with LyP is also supported by the high 41% frequency of associated lymphomas in the present study. This rate is higher than the commonly reported 10%-20% rates [3,8,9,[11][12][13][14][15]20], and is in accordance with the results from recent studies by Kunishige et al and Liu et al, who reported much higher rates of associated lymphomas (40% and 61%, respectively) [16][17][18]. It is likely that the high proportion of associated lymphomas in these 2 series and the present study (41%) are due to the prolonged follow-up of patients (17.5, 12.3, and 11.3 years respectively), as compared with series that reported lower rates of associated lymphomas [16,18].…”
Section: Discussionsupporting
confidence: 92%
“…However, in a recent study, only a mixed histological subtype was shown to correlate with increased risk for associated lymphoma in patients with LyP [20]. Older age has also been pointed as a risk factor for association between LyP and another lymphoma in one study [7], but this finding was not confirmed in a more recent and larger one [18].…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Lymphomatoid papulosis (LyP) is rhythmic paradoxical eruptions of erythematous papules and it has malignant histologic features and a benign clinical course 1 . Immunophenotyping studies of LyP lesions have shown a predominant CD4 expression.…”
Section: Introductionmentioning
confidence: 99%